Establishing Valid and Reliable Measures for Organizational Commitment and Job Performance: An Exploratory Factor Analysis - Ehido, Amauche; Awang, Zainudin; Halim, Bahyah Abdul; Ibeabuchi, Chukwuebuka (International Journal of Social Sciences Perspectives, 2020)
The sustainability of organizations is increasingly reliant on the involvement, loyalty, and, more importantly, the commitment of their employees. Organizational commitment (OC) is extensively studied in management literature as a predictor of employees’ job performance (JP). Several studies discovered a positive correlation between OC and JP among employees. However, most of these studies failed to conduct preliminary analyses on the measuring instruments for the above constructs to determine their appropriateness for other detailed analyses. Therefore, this study responded to the call by conducting a comprehensive Exploratory Factor Analysis (EFA) procedure to develop an effective instrument to measure OC and JP constructs. This study was based on a cross-sectional research design involving 100 randomly selected academics from five Malaysian research universities, and data was obtained using a structured self-administered questionnaire. The validity and reliability of the OC and JP instruments were established using EFA and reliability analysis. The results revealed that the 18 items measuring OC construct were grouped into four components, 1 item with factor loading below .6 was deleted, and 17 items were retained. The 13 items measuring the JP construct were grouped into two components, 1 item was also deleted for the same reason, and 12 items were retained for further analysis. All the components have high internal reliabilities (Cronbach’s Alpha > .785). Consequently, this study contributes to an improved understanding of the dimensions of OC among academics. The universities’ management should develop strategies to enhance the degree of employees’ commitment and efforts towards the organization.